DESIGN EVALUATION AND IMPROVEMENT OF TJ-24 TURBINE AND PROPELLING NOZZLE BY USING NUMERICAL SIMULATION OF FLUID FLOW - Jeremy Bonatua Sinaga, Michael
Turbojet TJ-24 is a micro turbojet engine that is made and developed by Mechanical Engineering Department of Institut Teknologi Bandung since 2002. TJ-24 is designed to produce thrust with the amount of 24 N. The main configurations of TJ-24 are intake, KJ66 centrifugal compressor and axial turbine, annular type combustion chamber, and convergent propelling nozzle. TJ-24 is designed to operate at 80000 rpm and mass flow rate at 0,133 kg/s. The last test done on TJ-24 gave the fact that the system was not capable to idle and produced thrust. Numerical simulation of fluid flow was conducted to check if the work produced by the turbine is with the amount of the work needed by the compressor, if and propelling nozzle will give 24 N thrust. Numerical simulation of fluid flow done on the turbine using ANSYS CFX 2019 R3 gave result that fluid velocity produced by Nozzle Guide Vane (NGV) was not sufficient to give the target rotational speed of the turbine at operating condition. Design improvements were conducted to turbine stator and rotor by changing the flow angle and reducing NGV’s outlet annulus area. Numerical simulation on the new design showed that the turbine will be able to produce work needed by the compressor to operate at the specified operating condition with mechanical efficiency requirement is to be 90 % or higher with 12386.35 J/s work produced. Numerical simulation conducted on the current propelling nozzle using the same software as previous simulations gave result that the thrust produced was with the amount of 25.5 N.